Effects of polysaccharide from fruiting bodies of Agaricus bisporus, Agaricus brasiliensis, and Phellinus linteus on alcoholic liver injury. (June 2014) - Uyanoglu, Mustafa; Canbek, Mediha; van Griensven, Leo J. L. D.; Yamac, Mustafa; Senturk, Hakan; Kartkaya, Kazım; Oglakcı, Aysegul; Turgak, Ozge; Kanbak, Gungor
Abstract In the present study, the curative effects of crude polysaccharides (PSs) from mushrooms on the symptoms of alcoholic liver injury were investigated. PSs from Agaricus bisporus, Agaricus brasiliensis, and Phellinus linteus fruiting bodies were administered by gavage at levels of 100 mg per kg body weight per day for 7 d after the onset of the disease. The caspase-3 activity, mitochondrial membrane potential, mitochondrial outer membrane integrity of the liver tissues of sacrificed rats, and the serum alanine aminotransferase (ALT) levels were determined. In addition, light and transmission electron microscope (TEM) studies were performed for histopathological and cytological evaluations on liver sections. PSs from A. brasiliensis decreased ALT level and mitochondrial membrane potential and increased the outer membrane integrity; microscopic examinations also revealed normal hepatocytes and tissue. On the basis of our data, it can be argued that crude PSs from Agaricus brasiliensis have therapeutic potential for alcoholic liver injury.